2021
DOI: 10.3390/math9232990
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Modelling of a Cracked Pressurized Cylindrical Structure by Using Extended Iso-Geometric Analysis (X-IGA)

Abstract: In this study, a NURBS basis function-based extended iso-geometric analysis (X-IGA) has been implemented to simulate a two-dimensional crack in a pipe under uniform pressure using MATLAB code. Heaviside jump and asymptotic crack-tip enrichment functions are used to model the crack’s behaviour. The accuracy of this investigation was ensured with the stress intensity factors (SIFs) and the J-integral. The X-IGA—based SIFs of a 2-D pipe are compared using MATLAB code with the conventional finite element method av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The effectiveness of the FEODM (Finite Element Over-Deterministic Method) was demonstrated in the work of R. Ayatollahi et al [30]. The benefit of the IG-ODM approach we have described compared to other ways employing ODM; the geometry and the crack are precisely represented [31][32][33] using the X-IGA method.…”
Section: Discussionmentioning
confidence: 88%
“…The effectiveness of the FEODM (Finite Element Over-Deterministic Method) was demonstrated in the work of R. Ayatollahi et al [30]. The benefit of the IG-ODM approach we have described compared to other ways employing ODM; the geometry and the crack are precisely represented [31][32][33] using the X-IGA method.…”
Section: Discussionmentioning
confidence: 88%
“…The statistics of papers submitted to this Special Issue for both published and rejected items are as follows: 23 total submissions, of which 16 were published (69.6%) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 7 rejected (30.4%). The authors' geographical distribution is shown in Table 1, where it can be seen that the 67 authors are from 13 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…Montassir, S. et.al. [14] describes the analysis of a mechanical system having cylindrical structure of in a beautiful way. The control system based modeling of a helicopter (including T.F) and proper numerical simu lation was described by the researcher Tarsi, A. et.al.…”
Section: Dynamics Of Mechanical System-a Literature Reviewmentioning
confidence: 99%